2014
DOI: 10.1007/s11064-014-1411-2
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Preconditioning-Induced Epileptic Tolerance by Upregulation of Monocarboxylate Transporter 4 Expression in Rat Hippocampal Astrocytes

Abstract: Noxious stimuli applied at doses close to but below the threshold of cell injury induce adaptive responses that provide a defense against additional stress. Epileptic preconditioning protects neurons against status epilepticus and ischemia; however, it is not known if the converse is true. During hypoxia/ischemia (H/I), lactate released from astrocytes is taken up by neurons and is stored for energy, a process mediated by monocarboxylate transporter 4 (MCT4) in astroglia. The present study investigated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The experiments presented here now show that lactate dampens the increase in neuronal excitability which was observed when glial metabolism is blocked. In line with this, a decreased MCT4 expression was shown in temporal lobe epilepsy 65 and an upregulation of MCT4 via hypoxic preconditioning was shown to protect against experimentally induced seizures 66 . In line with this, a decreased MCT4 expression was shown in temporal lobe epilepsy 65 and an upregulation of MCT4 via hypoxic preconditioning was shown to protect against experimentally induced seizures 66 .…”
Section: Discussionsupporting
confidence: 55%
“…The experiments presented here now show that lactate dampens the increase in neuronal excitability which was observed when glial metabolism is blocked. In line with this, a decreased MCT4 expression was shown in temporal lobe epilepsy 65 and an upregulation of MCT4 via hypoxic preconditioning was shown to protect against experimentally induced seizures 66 . In line with this, a decreased MCT4 expression was shown in temporal lobe epilepsy 65 and an upregulation of MCT4 via hypoxic preconditioning was shown to protect against experimentally induced seizures 66 .…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies suggested that Mcts are involved in the response to hypoxia and ischemia. For example, hypoxic preconditioning caused an upregulation of Mct4 in rat astrocytes [45] and a knockdown of Mct4 interfered with the survival of mixed astrocyte-neuron cultures under hypoxia [46]. Mct4 activity and structure appear to be associated to the astrocyte-specific excitatory amino acid transporter 1 (Eaat1) [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MCT4 has been demonstrated as expressed in the neurons of ob/ob obese mice, high-fat diet fed mice and also db/db diabetic mice (11). However, MCT4 immunoreactivity is observed in the astrocytes of control rats and mice (9)(10)(11)(12). This observation may be associated with characteristic factors in plasma lipid response to dietary carbohydrate and fatty acids previously reported in Mongolian gerbils; Mongolian gerbils have been reported to be more sensitive to fatty acids in the presence and absence of dietary cholesterol (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…MCT1 has been predominantly observed in the endothelial cells of microvessels and also in glial cells (7)(8)(9). In contrast, MCT2 and MCT4 isoforms have been observed in neurons and astrocytes (9)(10)(11)(12)(13)(14). Several studies have reported cell-specific changes in the expression of MCTs occurring in different rat models of ischemia (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%